Investigation of (n,2n) reactions using the high energy neutron facility at NCSR “Demokritos” - Vlastou, R.; Kalamara, A.; Kokkoris, M.; Serris, M.; Patronis, N.; Diakaki, M.; Spiliotis, A.; Georgoulakis, M.; Sigalos, D.; Hassapoglou, S.; Kobothanasis, K.; Krokidi, K.; et al. (HNPS Advances in Nuclear Physics, 2019)
In the high energy neutron facility at the 5.5MV tandem T11/25 Accelerator of NCSR "Demokritos", the neutron beam is produced by means of the 3H(d,n)4He reaction in the energy range 15-21 MeV and at a flux of the order of 105 -106 n/cm2s. The beam has been characterized by means of the NeuSDesc and MCNP5 Monte Carlo simulations along with the multiple foil activation technique at various neutron energies. The neutron flux has been deduced using reference reactions, such as the 27Al(n,α) reaction, while the flux variation of the neutron beam was monitored by using a BF3 detector. After the characterization, the neutron beam has been used for (n,2n) reaction cross section measurements on Hf, Au and Ir isotopes via the activation technique. The irradiations were carried out at 15.3 and 17.1 MeV.